Modal Sosial Sebagai Basis Ekonomi Masyarakat Suku Bugis Di Kabupaten Nunukan, Kalimantan Utara - Ramadini, Putri Puja; Rahman, Abdul (Research Agency for Humanity and Urban, 2023)
This research aims to find out: (1) The social capital applied by the Bugis tribe community so that they are able to create an economic base in the overseas lands of Nunukan Regency, North Kalimantan. (2) The efforts of the Bugis Tribe community to maintain social capital as an economic basis in Nunukan Regency, North Kalimantan. To achieve this goal, the researcher used a descriptive research type of qualitative approach by collecting data through observation, interviews and documentation. This research involved 7 informants. The results of this research show that: (1) The social capital of the Bugis tribe community in Nunukan Regency is divided into four forms, namely kinship and kinship relationships, social networks or associational life, cross-sector linkages, and compliance with cultural norms and values. Because they have these four social capitals, the Bugis people are able to create an economic base in Nunukan Regency